Gender-related differences in patient selection for and outcomes after pace and ablate for refractory atrial fibrillation: insights from a large multicenter cohort. (24th May 2021) - Baumgartner, T; Kaelin-Friedrich, M; Makowski, K; Noti, F; Schaer, B; Haeberlin, A; Badertscher, P; Baldinger, S; Seiler, J; Osswald, S; Kuehne, M; Roten, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: A pace & ablate strategy may be performed in cases of severe refractory atrial arrhythmias. Purpose: We aimed to assess gender related differences in patient selection and clinical outcomes after pace & ablate. Methods: In a retrospective multicenter study, patients undergoing AV-junction-ablation between 2011 and 2019 were studied. Gender-related differences in terms of baseline characteristics, device-related complications, heart failure (HF) hospitalisations and death were assessed. Results: Overall, 513 patients underwent AV-junction-ablation (median age 75 years, 50% males). At baseline, male patients were younger (72 vs. 78 years, p < 0.001), more frequently had non-paroxysmal AF (82% vs. 72%, p = 0.006), a lower LVEF (35% vs. 55%, p < 0.001) and more often received biventricular stimulation (75% vs. 25%, p < 0.001). Interventional complications were rare in both gender (1.2% vs 1.6%, p = 0.72). Following AV-junction-ablation, improvement of EHRA-class by ≥1 and of LVEF by ≥5% occurred in 44% and 19% of patients respectively, without gender differences (p = 0.66 and p = 0.38). Patients were followed for a median of 42 months in survivors (IQR 22-62). Lead-related complications (11 patients, 2.1%), infections (1 patient, 0.2%) and upgrade to ICD or CRT (18 patients, 3.5%) were rare. In Kaplan Meier analysis, HF hospitalisations during 4 years of follow-up were more common in men (22% vs 11%, p = 0.02), as were death (28% vs 21%, p = 0.02) and the combination of death or HF hospitalisation (37% vs. 26%, p = 0.008, Figure). Gender remained an independent predictor of the combined endpoint of death or HF hospitalisation after adjustment for age, LVEF and type of stimulation. Conclusion: A Pace & Ablate strategy is safe and results in improvement of EHRA class and LVEF in a substantial number of patients. We found significant gender differences in patient selection for pace & ablate. Female patients had a more favorable clinical course after AV-junction-ablation, which was independent of age, EF and type of stimulation.